2002
DOI: 10.1093/geronb/57.5.p453
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Change in Persons With Dementia: Relationships With Mental and Physical Health of Caregivers

Abstract: The purpose of this study was to examine the effects that changes in behavioral and psychological symptoms of dementia of persons with Alzheimer's disease have on their caregivers' mental health and physical health. The research design was a prospective, longitudinal follow-up study conducted in a major medical center and in participants' homes. Longitudinal analysis linking change in behavior to caregiver outcomes was based on 64 cases. Care recipients were assessed at the time of diagnosis with the Mini-Ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
82
4
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 34 publications
8
82
4
2
Order By: Relevance
“…(37;38) In our examination of mediators of the patient depression-caregiver depression relationship both impact on patient’s functioning and burden to caregiver were important. While caregiver burden has been previously shown to mediate the relationship between patient objective behavior and caregiver outcomes,(15;17;39) the role of impact on patient functioning in the causal pathway has not been previously explored. Our findings suggest that caregivers recognize the difficulty that patient depressive symptoms may cause for patients and that this mechanism may independently result in caregiver depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(37;38) In our examination of mediators of the patient depression-caregiver depression relationship both impact on patient’s functioning and burden to caregiver were important. While caregiver burden has been previously shown to mediate the relationship between patient objective behavior and caregiver outcomes,(15;17;39) the role of impact on patient functioning in the causal pathway has not been previously explored. Our findings suggest that caregivers recognize the difficulty that patient depressive symptoms may cause for patients and that this mechanism may independently result in caregiver depression.…”
Section: Discussionmentioning
confidence: 99%
“…Using this model, studies report that the association between objective stressors such as BPSD and mental and physical health outcomes of caregivers are mediated by subjective stress appraisal. (1517) Suffering may be another pathway by which BPSD results depression in caregivers(18) suggesting that perception of the patient’s quality of life and their ability to function daily may affect the caregiver by evoking empathy for the patient.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on this theme indicated the strong association of neuropsychiatric disorders with caregivers' health perception and stress 27 . A possible explanation for our results may be the lower prevalence of care recipients' behavioral neuropsychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…These BPSD occur in a dynamic process involving the patient, the family caregiver and their environment. They are known to be more stressful to caregivers than cognitive or functional decline, because are felt as the most difficult to manage (Donaldson et al, 1998;Hooker et al, 2002;Vugt et al, 2003;Matsumoto et al, 2007) and have a negative impact on the relationships between the caregiver, patient and family (Lyons et al, 2002). It has been reported that caregivers differ in their emotional responses to BPSD even when facing similar problems and the caregiver's perception of patient's problems is more important than problem behaviour 'per se' (Zarit, 1996;Vugt et al, 2005), furthermore, caregivers can interpret poorly and react inadequately to BPSD (Paton et al, 2004).…”
Section: Introductionmentioning
confidence: 99%